2019
DOI: 10.1038/s41467-019-10579-1
|View full text |Cite
|
Sign up to set email alerts
|

Directed propulsion of spherical particles along three dimensional helical trajectories

Abstract: Active colloids are a class of microparticles that ‘swim’ through fluids by breaking the symmetry of the force distribution on their surfaces. Our ability to direct these particles along complex trajectories in three-dimensional (3D) space requires strategies to encode the desired forces and torques at the single particle level. Here, we show that spherical colloids with metal patches of low symmetry self-propel along non-linear 3D trajectories when powered remotely by an alternating current (AC) electric fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(79 citation statements)
references
References 36 publications
1
78
0
Order By: Relevance
“…1A): (i) sensing the system state via particle tracking, i.e., the self-propelled particle positions and orientations and cargo position; (ii) calculating self-propulsion speeds of each particle based on the current state and desired future state (based on a control objective); and (iii) actuating each particle's speed by considering light-activated self-propelled colloids on a light array [e.g., a liquid-crystal display (35) screen surface]. Actuation could also be achieved on spatially addressable electrodes or other arrays that mediate locally actuated transport mechanisms (36)(37)(38)(39), which could modify some terms of the dynamic model, but the control problem would be conceptually similar.…”
Section: Controlling Colloidal Swarmsmentioning
confidence: 99%
“…1A): (i) sensing the system state via particle tracking, i.e., the self-propelled particle positions and orientations and cargo position; (ii) calculating self-propulsion speeds of each particle based on the current state and desired future state (based on a control objective); and (iii) actuating each particle's speed by considering light-activated self-propelled colloids on a light array [e.g., a liquid-crystal display (35) screen surface]. Actuation could also be achieved on spatially addressable electrodes or other arrays that mediate locally actuated transport mechanisms (36)(37)(38)(39), which could modify some terms of the dynamic model, but the control problem would be conceptually similar.…”
Section: Controlling Colloidal Swarmsmentioning
confidence: 99%
“…One such study showed that L-shaped particles exhibit circular trajectories. 22 More recent experiments on select anisotropic shapes or patches confirmed some of the predictions in 2D [23][24][25][26] and found unexpected motion patterns such as non-cylindrical helices 27 in 3D. Still, the current limitations in particle design prevent a systematic comparison with theory.…”
Section: Introductionmentioning
confidence: 89%
“…More recently, Lee et al [81] developed special spherical colloids with metal patches ( Figure 5A). When remotely powered by an AC electric field, these designed particles exhibited a predefined 3D helical movement along the axis of the field with a controllable speed and shape of trajectory turned by the applied field strength and patch geometry.…”
Section: Electric Fieldmentioning
confidence: 99%
“…Reproduced with permission. [81] Copyright 2019, Springer Nature. B) Schematic diagram of an interdigitated microelectrodes system where, upon the application of AC electric fields, metallodielectric Janus particles are hydrodynamically confined and electrokinetically propelled in one dimension along the electrode center lines with tunable speeds.…”
Section: Magnetic Fieldmentioning
confidence: 99%